The Role of the Inspectorate of West Pasaman Regency in Maintaining Unqualified Opinion (WTP) through the Review of Work Plans and Budgets (RKA) - Zakiah Darajat; Hendri Koeswara; Desna Aromatica (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
The purpose of this research is to describe and analyze the RKA review conducted by the West Pasaman District Inspectorate. In analyzing this research, the researcher used Permendagari Number 10 of 2018 concerning the Review of Development Planning Documents and the Annual Regional Budget, which is in the RKA review stage, where there is a Planning, Implementation and Reporting process. This type of research is qualitative with a descriptive approach. Interview data collection techniques, documentation and observation. Informants were selected using a purposive sampling technique. Data analysis used is data collection, data reduction, data presentation, and drawing conclusions. Data validation uses source triangulation. The results of the study show that the Inspectorate of West Pasaman Regency has guided Permendagri No. 10 of 2018 in general in implementing the RKA review as one of the supports for obtaining Unqualified opinion (WTP) by West Pasaman Regency, because planning needs to be considered early in anticipation of the occurrence of budgetary waste that can be detrimental to the region. The problems found in the implementation of this RKA review were the preparation of the Review Work Program (PRK) carried out by team members, in addition to that the implementation of the RKA review was not in accordance with the time specified in the Assignment Letter (SPT), due to the lengthy submission of supporting documents review by SKPD. However, there are still advantages to be gained from carrying out the RKA review at the West Pasaman District Inspectorate such as the implementation of Self-Office Training (PKS) in budget savings and the existence of tiered reviews in the implementation and reporting stages.